Neurotoxicity mechanism of aconitine in HT22 cells studied by microfluidic chip-mass spectrometry - Yingrui Zhang; Shiyu Chen; Fangfang Fan; Ning Xu; Xian-Li Meng; Yi Zhang; Jin-Ming Lin (Journal of Pharmaceutical Analysis, 2023)
Aconitine, a common and main toxic component of Aconitum, is toxic to the central nervous system. However, the mechanism of aconitine neurotoxicity is not yet clear. In this work, we had the hypothesis that excitatory amino acids can trigger excitotoxicity as a pointcut to explore the mechanism of neurotoxicity induced by aconitine. HT22 cells were simulated by aconitine and the changes of target cell metabolites were real-time online investigated based on a microfluidic chip-mass spectrometry system. Meanwhile, to confirm the metabolic mechanism of aconitine toxicity on HT22 cells, the levels of lactate dehydrogenase, intracellular Ca2+, reactive oxygen species, glutathione and superoxide dismutase, and ratio of Bax/Bcl-2 protein were detected by molecular biotechnology. Integration of the detected results revealed that neurotoxicity induced by aconitine was associated with the process of excitotoxicity caused by glutamic acid and aspartic acid, which was followed by the accumulation of lactic acid and reduction of glucose. The surge of extracellular glutamic acid could further lead to a series of cascade reactions including intracellular Ca2+ overload and oxidative stress, and eventually result in cell apoptosis. In general, we illustrated a new mechanism of aconitine neurotoxicity and presented a novel analysis strategy that real-time online monitoring of cell metabolites can provide a new approach to mechanism analysis.